2011
DOI: 10.1128/aem.01852-10
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin, Alkaline Phosphatase, and Aminopeptidase N as Receptors of Cry11Ba Toxin from Bacillus thuringiensis subsp. jegathesan in Aedes aegypti

Abstract: Cry11Ba is one of the most toxic proteins to mosquito larvae produced by Bacillus thuringiensis. It binds Aedes aegypti brush border membrane vesicles (BBMV) with high affinity, showing an apparent dissociation constant (K d ) of 8.2 nM. We previously reported that an anticadherin antibody competes with Cry11Ba binding to BBMV, suggesting a possible role of cadherin as a toxin receptor. Here we provide evidence of specific cadherin repeat regions involved in this interaction. Using cadherin fragments as compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 46 publications
(57 reference statements)
1
33
1
Order By: Relevance
“…In mosquito larvae, homologous APN, CAD-like, and alkaline phosphatase proteins have been described as Cry11 and Cry4 receptor proteins (6), and in Coleoptera a cadherin-like protein has been demonstrated to act as a Cry3Aa receptor (7). In coleopteran insects, other molecules, such as an ADAM-like metalloprotease (8) and alkaline phosphatase (9), have been proposed as putative Cry receptors.…”
mentioning
confidence: 99%
“…In mosquito larvae, homologous APN, CAD-like, and alkaline phosphatase proteins have been described as Cry11 and Cry4 receptor proteins (6), and in Coleoptera a cadherin-like protein has been demonstrated to act as a Cry3Aa receptor (7). In coleopteran insects, other molecules, such as an ADAM-like metalloprotease (8) and alkaline phosphatase (9), have been proposed as putative Cry receptors.…”
mentioning
confidence: 99%
“…Of particular interest, ALPs (EC 3.1.3.1; phosphomonoester hydrolases), ubiquitous enzymes widely found in microorganisms and animal kingdoms, are a highly conserved family of largely distributed cell surface and secreted metalloenzymes; many are GPI-anchored glycoproteins (for a review, see reference 13). To date, various ALPs from mosquitoes and other insect species have been reported as functional Cry toxin receptors, including Cry11Aa receptors from A. aegypti (8,9), Cry11Ba receptors from A. aegypti (12) and Anopheles gambiae (10), a Cry1Ab receptor from Manduca sexta (3), and Cry1Ac receptors from Helicoverpa armigera (14) and Heliothis virescens (17).…”
mentioning
confidence: 99%
“…Alternative splicing of the receptor gene due to transposable elements was shown to confer resistance to Bacillus sphaericus binary toxins in Culex pipiens populations (Darboux et al, 2007) but such mechanism has not been demonstrated so far for Bti toxins. Cross-resistance mechanisms between different Cry toxins have been reported, presumably involving shared membrane receptors (Siqueira et al, 2004;Zhao et al, 2001;Xu et al, 2010;Likitvivatanavong et al, 2011). In lepidopterans, four types of receptors for Cry1A have been identified: cadherin, glycosylphosphatidylinosytol (GPI)-anchored APN (aminopeptidase N), GPI-anchored ALP (alkaline phosphatase) and glycolipids (reviewed in Pigott & Ellar, 2007).…”
Section: The Role Of Membrane Receptors In Resistancementioning
confidence: 99%